Willingness to Pay for Solar Panels and Smart Grids - Tunç Durmaz; Aude Pommeret; Ian Ridley (Fondazione Eni Enrico Mattei (FEEM), 2017)
It is expected that the renewable share of energy generation will rise considerably in the near future. The intermittent and uncertain nature of renewable energy (RE) calls for storage and grid management technologies that can allow for increased power system flexibility. To assist policy makers in designing public policies that incentivize RE generation and a flexible power system based on energy storage and demandside management, better knowledge as to the willingness to pay for the corresponding devices is required. In this paper, we appraise the willingness of a household (HH) to pay for a 1.9 kW peak photovoltaic (PV) system and smart grid devices, namely, a smart meter and a home storage battery. Results indicate that having access to a storage device is key for the HH decision to install a smart meter. We also find that it is beneficial for the HH to install the PV system regardless of the pricing scheme and the ownership of the battery pack. It is, nevertheless, barely desirable to install the battery pack regardless of the presence of the PV system; an outcome pointing to the fact that the high cost of storage is a drawback for the wider use of these systems. When storage is constrained in such a way that only the generated power can be stored, the willingness to install the battery pack reduces even further. The investment decisions made when legislation prohibits net-metering are also analyzed.
Keywords: D12; D24; D61; Q41; Q42; 330; Renewable Energy; Intermittency; Distributed Generation; Smart Solutions; Energy Storage; Demand Response; Willingness to Pay